THE CONSTRAINTS OF EMBODIMENT AND LANGUAGE-THOUGHT RELATIONS - Prakash MONDAL (Studia Universitatis Babeș-Bolyai. Philosophia, 2021)
This paper aims to impugn the magnified role of specific natural languages in structuring and shaping cognition in the context of language-thought relations. Since language-thought interactions are being increasingly explored in different kinds of empirical studies showing or attempting to show context-specific or general influences of language over thought and thinking, there is reason to tame the excesses of language-specific influences over thought, thinking and cognition. In this regard, any context-specific influences of languages over thought and thinking in being grounded in certain modes/modalities of cognition must be governed by the constraints of body-world interactions that operate on modes/modalities of cognition. Thus, this paper will argue that language-specific influences over thought, thinking and cognition are possible to the extent that they are permitted by the constraints of embodiment.